The skull collectors : race, science, and America's unburied dead - Fabian, Ann (The University of Chicago Press, 2010)
"When Philadelphia naturalist Samuel George Morton died in 1851, no one cut off his head, boiled away its flesh, and added his grinning skull to a collection of crania. It would have been strange, but perhaps fitting, had Morton's skull wound up in a collector's cabinet, for Morton himself had collected hundreds of skulls over the course of a long career. Friends, diplomats, doctors, soldiers, and fellow naturalists sent him skulls they gathered from battlefields and burial grounds across America and around the world. With the Skull Collectors, eminent historian Ann Fabian resurrects that popular and scientific movement, telling the strange--and at times gruesome--story of Morton, his contemporaries, and their search for a scientific foundation for racial difference. From cranial measurements and museum shelves to heads on stakes, bloody battlefields, and the 'rascally pleasure' of grave robbing, Fabian paints a lively picture of scientific inquiry in service of an agenda of racial superiority, and of a society coming to grips with both the deadly implications of manifest destiny and the mass slaughter of the Civil War. Even as she vividly recreates the past, Fabian also deftly traces the continuing implications of this history, from lingering traces of scientific racism to debates over the return of the remains of Native Americans that are held by museums to this day."--Provided by publisher.